Pengaruh Duduk Tawaruk (Senam Maryam) Terhadap Robekan Perineum Pada Ibu Bersalin Primigravida - yayah Rokayah; Kadar kuswandi; Melly Halimatussa'adiah; Erlin Puspita; Tutik Iswanti (Universitas Pahlawan Tuanku Tambusai, 2026)
Perineal tears are one of the most common complications of vaginal delivery experienced by primigravida mothers and have the potential to cause physical and psychological effects during the postpartum period. Effective prevention through non-invasive interventions during pregnancy is crucial to improving the quality of delivery. One exercise that is thought to increase the elasticity of the perineal tissue is the tawaruk sitting position, which is part of Maryam gymnastics. This study aims to analyse the effect of sitting in the tawaruk position on the incidence of perineal tears in primigravida mothers. This study uses a quasi-experimental design with a single intervention group approach in primigravida mothers in their third trimester who regularly perform the tawaruk sitting exercise prior to delivery. The evaluation is carried out during the delivery process to observe the incidence of perineal tears. The results of the study indicate that performing the tawaruk sitting position during pregnancy is associated with a decrease in the incidence of perineal tears. This exercise contributes to improving the readiness and flexibility of the perineal tissue. Thus, the tawaruk sitting position can be recommended as part of the childbirth preparation programme for primigravida mothers